The impact of the picture reading strategy on developing the oral expression skills of the second intermediate grade students - Muntaha Fahad Breesam / Huda Mahmood Shakir ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current research aims to identify the impact of the picture reading strategy on developing the oral expression skills of the second intermediate grade students. In order to achieve the objectives of the current research, the two researchers followed the steps of the experimental approach by defining the research community represented by female students in the second intermediate grade, as for the research sample, it was represented by (60) female students, divided into two experimental and control groups, and a set of parities was conducted between the two groups, as well as preparing a questionnaire to measure oral expression.The experiment was applied, and the study reached the following results:There is an effect of the (picture reading) strategy on the oral expression of the second intermediate grade students.The students of the experimental group had a clear superiority over the students of the control group in the post-test of oral expression.